The problematic nature of unregistered trademarks: an insight of Zambian law with comparative lessons from the South African jurisdiction - Mukuka, Rodrick Chisala (Department of Commercial Law, 2025)
Unregistered trademarks are an important aspect of trademark law. Historically, the origins and use of trademarks dates to medieval times and the early developments are particularly obscure. Some legal scholars have however argued that it seems the Courts first began to protect ‘marks at the behest of traders in the sixteenth century acknowledging the fact that such signs operated as an indication of source…the Courts then felt that if another trader were allowed to use the same sign, this would allow fraud to be committed on the public. Considering this development, the initial trademark protection was provided by the Common law courts. The rationale then was that if a trader had already used a mark, he deserved some protection. Overtime, it was discovered that trademark protection through common law courts was increasingly becoming inadequate thus paving way to statutory rights and the attendant perceived exclusive rights. It is now apparent that enforcing unregistered marks rights under the dictates of Common law, has for some reason proved to be problematic under modern trademark law, which include but not limited to what is perceived to be inadequate statutory provisions in the local trademark laws and somewhat lack of precise judicial interpretation of the law itself. Both Zambia and South Africa practice a dual legal system, where Common law and statutory rights are recognised and enforced simultaneously. With this Common law commonality between the two countries, it would ordinarily be expected that the legal jurisprudence emanating from the two jurisdictions with regards to unregistered trademarks should be the same but regrettably, that has not been the case. Undoubtedly, Zambia has a dual legal system that has been modelled after English law and the current provisions under Section 12 of the Zambian Trademark Act specifically provides for the preservation of Common law rights. However, the preservation of these rights, suffered a setback in 2012 when the Zambian Supreme Court held that unregistered mark cannot be accorded protection under the Zambian Trademarks Act. Put simply, the effect of the Zambian decision in the case of DH Brothers (Pty) Limited v Olivine Industries (Pty) Limited Appeal No. 74/2010 is that unregistered trademarks cannot be accorded any form of protection under statutory law, confining proprietors of unregistered marks to a rather old and expensive remedy that lies in the tort of ‘passing off'. Whilst Zambia is still grappling with the issue of Common law rights and whether the Supreme Court must indeed consider reversing its decision, the approach that has been taken by South Africa; another SADC state is quite different. The South African Trademarks Act No. 194 of 1993 has similar provisions under its Section 36, which has preserved Common law rights. In line with Section 36 as read together with 10 (12) of the Act, South African Courts have risen to the occasion and interpreted the said provisions correctly. It is therefore this writer's contention that the South African's legal jurisprudence that has evolved around Sections 36 and 10 (12) of the South African Trademark Act, are dear lessons that the Zambian legal system can embrace. Unregistered trademarks and the attendant Common law rights are still a key component of Intellectual Property Law and for this reason, they must never be alienated from any legal system; Zambia inclusive.